Optimizing the Utilization of Potential Fisheries Resources in Coastal Communities - Ahmad Midrar (Journal La Lifesci, 2020)
Lack of fish catch is one of the problems faced by coastal communities. From the fish farming activities in the sea, the community can obtain enormous economic benefits and support the economic growth of the family through the sale of fish from aquaculture. The government has given the opportunity and responsibility to the community in managing its resources, where the community itself has a need, goals, and aspirations and the community also makes decisions for their welfare. Socialization is needed regarding the importance of keeping coral reefs because the benefits are very good for coastal communities. The challenge faced is because coastal communities are increasing the ability and knowledge of the community about the importance of protecting ecosystems and capturing fisheries that are safe for the environment.